PELATIHAN TEKNIK MENULIS KREATIF DAN TEKNIK PARAFRASE KARYA TULIS ILMIAH BAGI MAHASISWA UNIVERSITAS HALU OLEO - Sultrayansa, Sultrayansa; Ningtyas, Rita Ayu; Ulfa, Nur Isnaini; Hayunira, Sasadara; Lestari, Dian Trianita (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
The Community Service Program at Halu Oleo University, titled "Training in Creative Writing Techniques and Final Assignment Paraphrasing Techniques for Students of the Communication Science, Mathematics, Archeology and Plant Protection Study Program," aims to improve students' ability to produce various scientific papers and the ability to paraphrase in this scientific work so that the similarity percentage in the Turnitin test meets the reasonableness threshold standard. For example, Communication Science students must revise their final thesis assignments that do not meet the graduation threshold before taking the final thesis exam, up to a maximum of three rounds of testing. Of course, this takes a long time if students are not equipped with writing and paraphrasing skills in order to avoid being detected as plagiarized. This will almost certainly have an impact on the number of scientific works produced by students under the supervision of lecturers, as well as the timeliness with which students complete their studies at Halu Oleo University. During this training, students learn how to brainstorm ideas and put them into creative writing, as well as how to create a platform for expressing emotions and thoughts. Aside from that, some students can come up with several interesting titles to use as themes for writing their thesis at the end of their study period. The technique of paraphrasing scientific writing provides special insight for students regarding the need for originality of ideas and writing produced so that it becomes work that meets the rules of scientific writing. It also provides additional knowledge about how the Turnitin application and its algorithm work in detecting the level of similarity of a piece of writing, so that this can be a trigger for students to prioritize scientific writing that has a level of similarity that meets writing standards.